Dilema keberadaan pedagang kaki lima di bantaran Sungai Muaro Panjalinan - Reva Putri Hermanita; Irwan Irwan; Isnarmi Moeis; Susi Fitria Dewi (Journal of Education, Cultural and Politics, 2026)
The presence of street vendors on the banks of the Muaro Panjalinan River in Padang City creates a dilemma between the economic needs of small communities and the ecological function of the riverbank area, as well as the enforcement of spatial planning policies. This study aims to analyze the actual conditions of street vendor placement from a spatial, legal, and social interaction perspective. It also examines the dilemmas that arise in environmental, social, and economic dimensions. The study employed a qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and documentation studies with street vendors, local residents, community leaders, the Public Order Agency (Satpol PP), and the River Basin Office (BWS). The results indicate that street vendor placement developed spontaneously without spatial planning and exists under conditions of uncertain legality. This activity has resulted in a decline in the quality of the riverbank environment and increased ecological risks, giving rise to conflicts over the use of space and changing patterns of social interaction. However, it also serves as a primary source of livelihood for the vendors. These findings demonstrate an imbalance in the management of public space and the need for more integrative and equitable planning policies.